Target Organ Complications and Cardiovascular Events Associated With Masked Hypertension and White-Coat Hypertension: Analysis From the Dallas Heart Study - Tientcheu, Danielle; Ayers, Colby; Das, Sandeep R; McGuire, Darren K; de Lemos, James A; Khera, Amit; Kaplan, Norman; Victor, Ronald; Vongpatanasin, Wanpen (Journal of the American College of Cardiology, 2015)
Multiple epidemiological studies from Europe and Asia have demonstrated increased cardiovascular risks associated with isolated elevation of home blood pressure (BP) or masked hypertension (MH). Previous studies have not addressed cardiovascular outcomes associated with MH and white-coat hypertension (WCH) in the general population in the United States. The goal of this study was to determine hypertensive target organ damage and adverse cardiovascular outcomes associated with WCH (high clinic BP, ≥140/90 mm Hg; normal home BP, <135/85 mm Hg), MH (high home BP, ≥135/85 mm Hg; normal clinic BP, <140/90 mm Hg), and sustained hypertension (high home and clinic BP) in the DHS (Dallas Heart Study), a large, multiethnic, probability-based population cohort. Associations among WCH, MH, sustained hypertension, and aortic pulsed wave velocity by magnetic resonance imaging; urinary albumin-to-creatinine ratio; and cystatin C were evaluated at study baseline. Then, associations between WCH and MH with incident cardiovascular outcomes (coronary heart disease, stroke, atrial fibrillation, heart failure, and cardiovascular death) over a median follow-up period of 9 years were assessed. The study cohort comprised 3,027 subjects (50% African Americans). The sample-weighted prevalence rates of WCH and MH were 3.3% and 17.8%, respectively. Both WCH and MH were independently associated with increased aortic pulsed wave velocity, cystatin C, and urinary albumin-to-creatinine ratio. Both WCH (adjusted hazard ratio: 2.09; 95% confidence interval: 1.05 to 4.15) and MH (adjusted hazard ratio: 2.03; 95% confidence interval: 1.36 to 3.03) were independently associated with higher cardiovascular events compared with the normotensive group, even after adjustment for traditional cardiovascular risk factors. In a multiethnic U.S. population, both WCH and MH were independently associated with increased aortic stiffness, renal injury, and incident cardiovascular events. Because MH is common and associated with an adverse cardiovascular profile, home BP monitoring should be routinely performed among U.S. adults.